Viability Assessment of Genipa americana L. (Rubiaceae) Embryonic Axes after Cryopreservation Using In Vitro Culture - Izulmé Rita Imaculada Santos; Antonieta Nassif Salomão (International Journal of Agronomy, 2016)
Embryonic axes excised from seeds of Genipa americana L. desiccated to different water contents were successfully cryopreserved by rapidly plunging seed samples directly into liquid nitrogen. Control and cryopreserved embryonic axes were excised and grown in WPM culture medium for viability assessment. All control embryonic axes (−LN2) excised from fully hydrated seeds (43.89% moisture content) germinated after 21 days of culture in vitro. These high germination percentages persisted even after the water content of the seeds was as low as 6.79%. After freezing in liquid nitrogen high germination percentages, 93%, 96%, and 93%, were observed for embryonic axes excised from seeds dehydrated to 13.26%, 9.57%, and 6.79 moisture content, respectively. The cryopreservation technique described here is recommended for long term conservation of G. americana germplasm.